2016
DOI: 10.1103/physrevd.93.124070
|View full text |Cite
|
Sign up to set email alerts
|

Mass decomposition of SLACS lens galaxies in Weyl conformal gravity

Abstract: We study here, using the Mannheim-Kazanas solution of Weyl conformal theory, the mass decomposition in the representative subsample of 57 earlytype elliptical lens galaxies of the Sloan Lens Advanced Camera for Surveys (SLACS) on board the Hubble Space Telescope (HST). We begin by showing that the solution need not be an exclusive solution of conformal gravity but can also be viewed as a solution of a class of f (R) gravity theories coupled to non-linear electrodynamics thereby rendering the ensuing results mo… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 128 publications
0
5
0
Order By: Relevance
“…Previously, this has been done by Cutajar and Adami [38] using the deflection formulas obtained by [23,26,27]. More recently, an analysis inspired by [37] was conducted by [39]. Since we have updated these formulas to exact expressions, it would be worthwhile to revisit the observational data using Eq.…”
Section: Resultsmentioning
confidence: 99%
“…Previously, this has been done by Cutajar and Adami [38] using the deflection formulas obtained by [23,26,27]. More recently, an analysis inspired by [37] was conducted by [39]. Since we have updated these formulas to exact expressions, it would be worthwhile to revisit the observational data using Eq.…”
Section: Resultsmentioning
confidence: 99%
“…The coefficientε ≡ c 1 in Equation ( 16), is intended to recover the cosmological constituents of the spacetime and, here, has the dimension of m −2 . Accordingly, the lapse function (15) provides the exterior geometry of the CWBH. In the adopted geometric system of units, Q and λ have the dimensions of m. For λ > Q, this spacetime allows for two horizons; an event horizon r + , and a cosmological horizon r ++ (instead of a Cauchy horizon), given by [55] r…”
Section: The Black Hole Solutionmentioning
confidence: 99%
“…The exterior geometry of the RCWBH is, therefore, specified by applying the lapse function (15), which provides…”
Section: The Rotating Counterpartmentioning
confidence: 99%
See 1 more Smart Citation
“…A series of dynamical solutions in CG were found in [36]. Mass decomposition of the lens galaxies of the Sloan Lens Advanced Camera for Surveys in CG was discussed in [37]. Recently it was indicated that conformal gravity can potentially test well against all astrophysical observations to date [38].…”
Section: Introductionmentioning
confidence: 99%